Kimiyaus Sa’adah: Exploring the Meaning of the Heart according to Imam Ghazali’s Perspective - Anshori, A.M.Miftah; Daud, Fathonah K. (Proceedings of International Conference on Muslim Society and Thought, 2024)
This research aims to describe the term heart according to Imam Ghazali’s perspective in his book entitled Kimiyaus Sa’adah. This research is descriptive qualitative research in a literature review form, using content analysis techniques from the book Kimiyaus Sa’adah. Based on this research, Imam Ghazali explained that the heart or "al-qalbu" is the main controller or "al-maliku" which can command its troops in the form of reason and all its devices including the human senses so that it becomes the cause of the happiness through good management or in Imam Ghazali’s words known by akhlaqul hasani management.